2020
DOI: 10.1177/0042085920902256
|View full text |Cite
|
Sign up to set email alerts
|

The Collateral Damage of In-School Suspensions: A Counterfactual Analysis of High-Suspension Schools, Math Achievement and College Attendance

Abstract: Even the least severe forms of exclusionary discipline are associated with detrimental effects for students that attend schools that overuse them. With a nationally representative longitudinal study of high school students, we utilize propensity score weighting to limit selection bias associated with schools that issue high numbers of in-school suspensions. Accounting for school social order and individual suspensions, we find that high-suspension schools are negatively associated with students’ math achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…These high social-control schools-with high rates of surveillance and punishment relative to the level of disorder and misbehavior-also subject non-offending students to negative, indirect, or collateral effects (Perry & Morris, 2014). An excessive reliance on discipline produces racial disparities when it occurs in schools with higher rates of segregation for Black and Latinx students, which increases their rates of exposure to surveillance and punishments (see Jabbari & Johnson, 2019a). As racial segregation tends to characterize entire metropolitan areas (Johnson, 2017) and segregated schools tend to have higher levels of social control (Jabbari & Johnson, 2019a), segregation severely limits the ability of Black and Latinx families to choose schools with proportionate rates of discipline and less racial disparity.…”
Section: Conceptualizing Disparities In Disciplinementioning
confidence: 99%
See 3 more Smart Citations
“…These high social-control schools-with high rates of surveillance and punishment relative to the level of disorder and misbehavior-also subject non-offending students to negative, indirect, or collateral effects (Perry & Morris, 2014). An excessive reliance on discipline produces racial disparities when it occurs in schools with higher rates of segregation for Black and Latinx students, which increases their rates of exposure to surveillance and punishments (see Jabbari & Johnson, 2019a). As racial segregation tends to characterize entire metropolitan areas (Johnson, 2017) and segregated schools tend to have higher levels of social control (Jabbari & Johnson, 2019a), segregation severely limits the ability of Black and Latinx families to choose schools with proportionate rates of discipline and less racial disparity.…”
Section: Conceptualizing Disparities In Disciplinementioning
confidence: 99%
“…Consider, for example, that schools with higher proportions of racial/ethnic minority students tend to have increased levels of surveillance in the built environment (Kupchik & Ward, 2014), more restrictions on dress and hairstyles (DaCosta, 2006; Ibrahim, Barnes, Butler-Barnes & Johnson, 2019), and more regimented and regulated approaches to learning (Goodman, 2013). These heightened regulations of behavior relate to higher dropout rates in predominantly minority schools (Jabbari & Johnson, 2019a).…”
Section: Policy Variation Between Schoolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found that in-school suspension significantly reduced drug-related offenses (Morrison et al 2001). Additionally, in some studies, in-school and out-of-school suspension were combined, noting the cumulative effect of suspension on academic achievement (Jabbari and Johnson 2020a;Mizel et al 2016;Morris and Perry 2016), and found significant disparities between students across race/ethnicity and social classwith an overrepresentation in African American students and those from low-income and urban school settings (Jabbari and Johnson 2020a). Our study builds on this scholarship by examining the impact of in-school suspension on the mathematics course-taking pipeline among Black girls.…”
Section: Literature Reviewmentioning
confidence: 88%